THE CORRELATION OF KNOWLEDGE ABOUT BREAST CANCER WITH EXAMINATION BEHAVIOR OF SELF BREAST EXAMINATION FOR FERTILE TIME WOMEN IN KURAHAN I, SANDEN BANTUL YOGYAKARTA - Lutfi, Nurni; Lubis, Dina Putri Utami; Kora, Firmina Theresia (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2020)
ABSTRACT Background: The incidence of breast cancer in Indonesia reaches 40 cases per 100,000 population. Early detection is a very important first step to determine the presence of a tumor or lump in the breast so that it can reduce the death rate. Knowledge is a factor that can shape the behavior of women of childbearing age to do Self Breast Examination (SADARI). Objective: To determine the relationship between knowledge about breast cancer and self breast examination behavior in Fertile Women in Kurahan I, Sanden Multigading, Bantul, Yogyakarta. Method: This study is a quantitative correlation with a cross sectional approach. The study population was 143 fertile women aged 15-49 years. The research sample of 59 respondents was determined by accidental sampling technique. The research instrument was a knowledge and behavior questionnaire about breast cancer. The data analysis techniques using Chi Square test. Results: Knowledge of breast cancer in women of childbearing age is in the sufficient category of 45.76%. The behavior about breast cancer in women of childbearing age is in the positive category of 69.49%. There is a correlation between knowledge and behavior about breast cancer in women of childbearing age based on the value of X2 count (24,126) > X2 table (5,991) and the Sig. (0,000) < α (0.05). Conclusion: There is a relationship between knowledge and behavior about breast cancer in women of childbearing age in the Kurahan 1, Murtigading, Sanden, Bantul, Yogyakarta.